Intra-Aneurysmal Pressure and Flow Changes Induced by Flow Diverters: Relation to Aneurysm Size and Shape - Larrabide, I.; Aguilar, M.L.; Morales, H.G.; Geers, A.J.; Kulcsár, Z.; Rüfenacht, D.; Frangi, A.F. (American Journal of Neuroradiology, 2013)
BACKGROUND AND PURPOSE: Effects of blood flow modification by flow diverters are observed to lead often to aneurysm thrombosis and reverse remodeling. For this process, to further understand the potential roles of intra-aneurysmal blood pressure changes and aneurysm morphologies, 23 patients were studied by numeric simulation. MATERIALS AND METHODS: 3D imaging of aneurysms of different sizes and shapes, all located at the supraclinoid segment of the ICA (n = 23), was prepared for CFD simulations. Hemodynamic variables were calculated for conditions before and after virtual FD implantation, reconstituting a vessel wall scaffold across the aneurysm neck. WSS, velocity, residence time, turnover time, and intra-aneurysmal pressure were assessed statistically. RESULTS: After placement of FDs, significant reductions inside the aneurysm were observed for most hemodynamic variables (P < .01) except mean intra-aneurysmal pressures. For minimum/maximum intra-aneurysmal pressure values, small but significant changes were found; however, they were considered too small to be of relevance. CONCLUSIONS: Calculations in 23 cases did not reveal significant intra-aneurysmal mean or peak pressure changes, indicating a minor role of pressure changes in the rare event of secondary ruptures after FD use. Other hemodynamic variables (WSS and velocity) exhibited more significant changes, indicating their role in intra-aneurysmal thrombus formation. Size-dependent, significantly higher reduction in WSS (P = .069) and velocity (P = .013) was observed in small aneurysms compared with larger ones. When it came to shape, there were significantly higher reductions in WSS (P = .055) and velocity (P = .065) and a significantly higher increase in turnover time in fusiform aneurysms compared with saccular aneurysms. CFDcomputational fluid dynamicsFDflow diverterIAintracranial aneurysmWSSwall shear stress